Rare complications after esophagectomy: incidence, clinical features, risk factors, management, and prevention - Guoqing Zhang; Jia Jiao; Long Qiu; Zheng Ding; Jia Zhao; Xue Pan; Xiangnan Li (Therapeutic Advances in Gastroenterology)
In recent years, common postoperative complications after esophagectomy have received increasing attention. However, the attention paid to rare complications, which often lead to serious consequences if they are not diagnosed in a timely manner, has not been sufficient. In this article, we present both the clinical and imaging features of rare complications following esophagectomy and strategies for their prevention and management. These rare complications are classiﬁed into four groups: esophageal substitute-related complications, thoracic duct-related complications, hernia-related complications, and transmural Hem-o-lok clip migration. Esophageal substitute-related complications include redundant conduits and conduit necrosis. We further classify redundant conduits as length-redundant conduits, width-redundant conduits, or a combination of both redundancies. Thoracic duct-related complications include refractory chylothorax and chylomediastinum. Refractory chylothorax is chylothorax refractory to well-established medical, interventional, and even surgical strategies, whereas chylomediastinum is a rare condition characterized by the accumulation of chyle in the mediastinum. Hernia-related complications are subclassified as hiatal hernias, retrocardiac lung hernias, intercostal lung hernias, trocar-site hernias, hernias internal to the retrosternal space or pericardium, and mesenteric defects. Transmural Hem-o-lok clip migration includes penetration of the trachea, conduit, or both. Thoracic surgeons should familiarize themselves with the rare complications of esophagectomy, most of which are serious conditions that require early and accurate diagnosis for proper management. The choice of intervention for rare complications depends on factors such as the patient’s general condition, the specific type of complication, the complication severity, the reconstruction route, the available medical resources, and the surgeon’s preference. To minimize the risk of these complications, esophagectomy and prevention methods need to be standardized.